2019
DOI: 10.3390/nu11020245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Energy Restriction on Eating Behavior Traits and Psychobehavioral Factors in the Low Satiety Phenotype

Abstract: Studies have shown that individuals with low satiety efficiency may be more susceptible to weight gain, but little is known about the effect of weight loss intervention outcomes in these individuals. This study aimed to evaluate the impact of an energy-restricted weight loss intervention on eating behavior traits and psychobehavioral factors in individuals differing in their satiety responsiveness. A pooled cohort of individuals who were overweight or obese (n = 100; aged 39 ± 9 years) participating in a 12- t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
7
24
0
1
Order By: Relevance
“…One study in men reported that the LSP lost less body weight after a 16-week diet compared to the HSP (15) . Whereas another study using male and female participants reported no effects of the LSP on weight change (22) . As such, further studies which investigate specific samples (e.g.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…One study in men reported that the LSP lost less body weight after a 16-week diet compared to the HSP (15) . Whereas another study using male and female participants reported no effects of the LSP on weight change (22) . As such, further studies which investigate specific samples (e.g.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, the current findings confirm that the LSP is linked with poorer weight loss outcomes, and extends this finding to women. Yet, not all studies have reported that the LSP is linked with less weight loss, with one study reporting no effects (22) . To explain the mixed findings it has been suggested that the LSP may be particularly influential when participants are following a satiating diet, and less influential when the LSP are following an energy restricted diet (22) .…”
Section: Appetite Control During the Programmentioning
confidence: 99%
“…For studies that used electronic VAS, one used 100 mm scales (18) , one used 60 mm scales (21) and one did not specify the length of the scale used (23) . Albert et al (38) L N R L M L L Arguin et al (40) H NR NR M NR L Arguin et al (12) L N R N R M M L Au-Yeung et al (30) L NR NR M NR L Beaulieu et al (25) L N R N R M H L Beaulieu et al (59) L N R M M M L Bédard et al (49) H (58) L L NR M L L Carbonneau et al (52) L NR NR M NR L Caudwell et al (57) H (26) L L L M L N R Chaput et al (47) H (14) L NR NR M NR L Defries et al (22) L NR NR H NR L Drapeau et al (8) H N R L M N R L Drapeau et al (10) H N R M M L L Drapeau et al (13) H N R N R L H N R Drapeau et al (53) H N R N R M H L Dubé et al (7) L NR NR M NR L Felix et al (32) L NR NR M NR NR Felix et al (36) L NR NR M NR NR Fillon et al (39) L (33) M NR NR M NR NR Green et al (6) H NR NR M NR NR Halford et al (56) M L L M M L Hansen et al (18) L N R M M N R L Harrington et al (43) H N R N R M L N R Hintze et al (54) L N R N R M H L Hollingworth et al (15) L N R N R N R N R N R Hopkins et al (19) L NR NR M NR NR Jönsson et al (44) L N R N R H H N R Jönsson et al (55) L (34) L L L M M N R King et al (50) H (27) L N R N R M H L McNeil et al (29) H NR NR M NR L McNeil et al (9) H …”
Section: Methodsmentioning
confidence: 99%
“…prev. post-menopause in women) (9,10,(44)(45)(46)(47)(48)(49)(50)(51)(52)(54)(55)(56)(57)59) , while three of these nineteen studies used SQ as a tool to classify the population as low and high satiety phenotype (12,53,58) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation